2020
DOI: 10.1002/cbdv.201900556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design, Synthesis and Docking Study of Alkyl and Benzyl Derivatives of Robustic Acid as Topoisomerase I Inhibitors

Abstract: Robustic acid is reported to be a bioactive compound, isolated from the medicinal plant Dalbergia benthamii Prain. Ten alkyl and benzyl derivatives (2a–2j) of robustic acid were designed and synthesized based on molecular docking approaches. The biological activities of most of the synthesized compounds (such as 2g, 2h, and 2i) were closely consistent with the docking results. In particular, 4‐O‐phenylpropyl substituted compound 2g displayed potent topoisomerase I inhibitory activity as well as cytotoxicity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Supplementary Materials: The following are available online. Supplementary File: MS, 1 H-NMR and 13 C-NMR spectra of compounds of RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementary Materials: The following are available online. Supplementary File: MS, 1 H-NMR and 13 C-NMR spectra of compounds of RA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Topo I inhibitor activity could be the basis of anti-tumor activity [ 16 , 17 ]. In the previous report, we chose the conformation with the highest score (7.89) for analysis [ 13 ], and the differences with this manuscript were the hydrophobic residue and bond length. Nevertheless, they all indicated that the hydrophobic interactions between the benzene ring of RA and hydrophobic residues of the Topo I-DNA complex were likely to be responsible for the stability of the docked complex, RA inhibiting the Topo I activity in an allosteric manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation